The Effect of Extracurricular Activities and Learning Motivation on the Students’ Mathematics Learning Achievement - Aswandi Aswandi; Rita Lefrida; Pathuddin Pathuddin; Alfisyahra Alfisyahra (IKIP Mataram, 2024)
This study aims to show (1) there is a significant positive effect of extracurricular activities on students' mathematics learning achievement at SMAN 2 Tolitoli (2) there is a significant positive effect of learning motivation on students' mathematics learning achievement at SMAN 2 Tolitoli (3) there is a significant positive effect of extracurricular activities and learning motivation on students' mathematics learning achievement at SMAN 2 Tolitoli. The sample used in this study amounted to 59 people from class XI MIPA. The instruments used in this study are questionnaires to see the perceptions of students regarding extracurricular activities and learning motivation, and the final grades of students' semester exams to see how students' mathematics learning achievement is. The data of this study were analysed using descriptive statistics and inferential statistics. The results obtained from this study are (1) there is a significant positive effect of extracurricular activities on student mathematics learning achievement with a contribution of 14.5% (2) there is a significant positive effect of learning motivation on student mathematics learning achievement with a contribution of 9.9%, (3) there is a significant positive effect of extracurricular activities and learning motivation on student mathematics learning achievement with a contribution of 16.1%. Further research is needed to deepen the influence of extracurricular activities and learning motivation on students' mathematics learning achievement. Further research is also needed to look at other factors that influence mathematics learning achievement, so that it can be of concern to teachers.